2014
DOI: 10.3389/fncel.2014.00209
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of the KCNT1 Slack channel in intellectual disability

Abstract: The sodium-activated potassium KNa channels Slack and Slick are encoded by KCNT1 and KCNT2, respectively. These channels are found in neurons throughout the brain, and are responsible for a delayed outward current termed IKNa. These currents integrate into shaping neuronal excitability, as well as adaptation in response to maintained stimulation. Abnormal Slack channel activity may play a role in Fragile X syndrome, the most common cause for intellectual disability and inherited autism. Slack channels interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 132 publications
5
85
0
Order By: Relevance
“…Slack channels play major roles in excitability in many brain regions by regulating adaptation of firing during sustained activity and by setting a high temporal accuracy of APs, essential in many forms of sensory processing (Kim et al, 2014). Mutations in the Slack channel have been linked to childhood seizures and severe forms of intellectual disability (Kim and Kaczmarek, 2014), implicating altered activity of this channel in the absence of FMRP as an important contributor to excitability defects in FXS (Zhang et al, 2012). …”
Section: Intrinsic Excitability: Expression and Modulation Of Ion Chamentioning
confidence: 99%
“…Slack channels play major roles in excitability in many brain regions by regulating adaptation of firing during sustained activity and by setting a high temporal accuracy of APs, essential in many forms of sensory processing (Kim et al, 2014). Mutations in the Slack channel have been linked to childhood seizures and severe forms of intellectual disability (Kim and Kaczmarek, 2014), implicating altered activity of this channel in the absence of FMRP as an important contributor to excitability defects in FXS (Zhang et al, 2012). …”
Section: Intrinsic Excitability: Expression and Modulation Of Ion Chamentioning
confidence: 99%
“…Human mutations in K Na 1.1 result in a variety of early onset epilepsies associated with very severe intellectual disability (Kim and Kaczmarek, 2014). These include malignant migrating partial seizures in infancy (Barcia et al, 2012;Ishii et al, 2013;McTague et al, 2013;Rizzo et al, 2016), autosomal dominant frontal lobe epilepsy (Heron et al, 2012;, Ohtahara syndrome , and other epilepsies (Juang et al, 2014;Vanderver et al, 2014).…”
Section: The K Ca 2 Family-small Conductance Channels Regulated mentioning
confidence: 99%
“…Along the same lines, the role of Ca 2+ -and voltage-activated potassium channels of big-conductance (BKs), which are highly related to Slack, have been well established in hippocampal-dependent learning tasks and memory (Matthews et al 2008;Typlt et al 2013). The relevance of neuronal Slack channels in behavioral functions, motor skills, or learning and memory processes in vivo is unclear, but recent studies on a series of gain-of-function mutations in the human Slack channel gene all revealed severe intellectual disability and developmental delay coupled to different early-onset epileptic syndromes in affected patients, suggesting that Slack may indeed play an important role in cognition and intellectual development (Aminkeng 2012;Barcia et al 2012;Heron et al 2012;Kaczmarek 2013;Kim and Kaczmarek 2014;Martin et al 2014).…”
mentioning
confidence: 99%